Hydrogen Production by Steam Reforming of Fusel Oil Using a CeCoOx Mixed‐Oxide Catalyst. Issue 4 (19th December 2019) - Sumrunronnasak, Sarocha; Reubroycharoen, Prasert; Pimpha, Nuttaporn; Chanlek, Narong; Tantayanon, Supawan
Abstract: Various CeCoOx mixed‐oxide catalysts with different Ce/Co ratios were prepared by surfactant‐assisted template precipitation of CeO2 and Ce3 O4 . The obtained catalysts were characterized by X‐ray diffraction, X‐ray photoelectron spectra, hydrogen temperature‐programmed reduction, nitrogen physisorption, and transmission electron microscopy. In general, the mixed‐oxide CeCoOx catalysts showed well‐dispersed CeO2 and Co3 O4 and good catalytic characteristics including a high specific surface area and porous structure. The effectiveness of the prepared catalysts on the hydrogen (H2 ) production from steam reforming of fusel oil was studied in a packed‐bed reactor. Co played an important role in C–C scission to break down the large C2–5 molecules into smaller species resulting in H2 formation. Ce could provide supplementary active oxygen to prevent coke formation on Co, resulting in a more stable activity of the mixed‐oxide catalyst throughout the reaction course. Abstract : CeCoOx mixed oxides prepared from CeO2 and Co3 O4 proved to be effective catalysts for H2 production from the steam reforming of fusel oil. The optimum catalyst composition Ce0.6 Co0.4 Ox exhibited a higher H2 yield and fusel oil conversion level and a narrower distribution of by‐products compared to pure oxides. It converts fusel oil into clean and more versatile H2 for various applications.